Children’s belief- and desire-reasoning in the temporoparietal junction: evidence for specialization from functional near-infrared spectroscopy - Bowman, Lindsay C.; Kovelman, Ioulia; Hu, Xiaosu; Wellman, Henry M. (Frontiers in Human Neuroscience, 2015)
Behaviorally, children’s explicit theory-of-mind (ToM) proceeds in a progression of mental-state understandings: developmentally, children demonstrate accurate explicit desire-reasoning before accurate explicit belief-reasoning. Given its robust and cross-cultural nature, we hypothesize this progression may be paced in part by maturation/specialization of the brain. Neuroimaging research demonstrates that the right temporoparietal junction (TPJ) becomes increasingly selective for ToM reasoning as children age, and as their ToM improves. But this research has narrowly focused on beliefs or on undifferentiated mental-states. A recent ERP study in children included a critical contrast to desire-reasoning, and demonstrated that right posterior potentials differentiated belief-reasoning from desire-reasoning. Taken together, the literature suggests that children’s desire-belief progression may be paced by specialization of the right TPJ for belief-reasoning specifically, beyond desire-reasoning. In the present study, we tested this hypothesis directly by examining children’s belief- and desire-reasoning using functional near-infrared spectroscopy (fNIRS) in conjunction with structural MRI to pinpoint brain activation in the right TPJ. Results showed greatest activation in the right TPJ for belief-reasoning, beyond desire-reasoning, and beyond non-mental reasoning (control). Findings replicate and critically extend prior ERP results, and provide clear evidence for a specific neural mechanism underlying children’s progression from understanding desires to understanding beliefs.